Evaluation of hematological markers in minor head trauma in the emergency room. - Acar, E.; Demir, A.; Alatas, Ö.; Beydilli, H.; Yıldırım, B.; Kırlı, U.; Hazer, D.; Kılınç, M.; Karagöz, Ü.; Derin, S. (European Journal of Trauma & Emergency Surgery, 2016)
Introduction: A rule exists regarding the use of computed tomography (CT) for patients presenting to the emergency department with head trauma and a Glasgow coma score (GCS) of 15; however, it can be difficult to make this decision due to overcrowded emergency rooms or exaggerated patients complaints. We evaluated patients who presented to the emergency room with minor head trauma, and we aimed to investigate the relationship between brain pathology on CT and hematological markers in order to find markers that help us identify brain pathology in patients with a GCS of 15. Methods: This retrospective study included 100 patients with pathologies present on their CT scans and a control group consisting of 100 patients with a normal CT. All data obtained from this study were recorded and evaluated using 'Statistical Package for Social Sciences for Windows 20' program. Parametric tests (independent samples test) were used with normally distributed data, while non-parametric tests (Mann-Whitney U test) were used with non-normally distributed data. A p ≤ 0.05 was considered significant. Finding: When we divided the cases into two groups based on the presence of pathologies on CT scan, we determined that there were significant differences between the groups in terms of white blood cell (WBC), hemoglobin (Hb), mean platelet volume (MPV), neutrophil (neu), troponin T, neutrophil/lymphocyte ratio (NLR) and platelet/lymphocyte ratio (PLR). When differentiating the patients that had brain pathologies on CT scan from patients that had normal CT scans, the troponin T cut-off value of 6.16 lead to 90 % specificity, and setting the NLR cut-off value at 4.29 resulted in a specificity of 90 %. Conclusion: MPV, NLR, and troponin T can be used as parameters that indicate brain pathologies on CT scans of patients presenting to the emergency department with isolated minor head trauma and GCS of 15 when the necessity of a CT scan is otherwise unclear.